PENGARUH PERUBAHAN KOMPOSISI JAKARTA ISLAMIC INDEX TERHADAP RETURN SAHAM - Ulfi Kartika Oktaviana, Nanik Wahyuni (lp2m-uin malang, 2011)
Objective of this study is to test wether the announcement of JII (Jakarta Islamic Index) composition change has information content and thus reacted by market as reflected in average abnormal return (AAR). The information content was tested using event study method to observe abnormal return surrounding JII composition change announcement day. Using data from JII since 2004 through 2010, the result of the study shows that there are abnormal return exist surrounding JII composition change announcement day. AAR is found statistically negative and significant different from zero for stock included-in and stock removed from JII. It indicates that the announcement having an information content. However, there is no significant difference of abnormal return found before and after announcement day. It might be caused by the regular timing of the composition change announcement and information leakage in form of “noise”. Thus, Indonesian stock market proves to be inefficient in its semistrong form.Keywords: JII composition change, shariah-compliant index, event study, abnormal return,market efficiency